서울시 일부 학부모의 나트륨 관련 식행동 및 미취학 자녀의 식행동과의 관련성 - 김예슬(Ye Seul Kim); 이홍미(Hong Mie Lee); 김정희(Jung Hee Kim) (Korean journal of community nutrition, 2015)
Objectives: The purpose of this study was to examine mothers' eating behavior and salty taste and its relationship to their preschool children's eating behaviors. Methods: This survey was conducted by self-report after getting permission from sixty one mothers who had preschool children. The questionnaire was focused on mothers' salty test and salt-related eating behavior of both mothers and their preschool children. Results: Comparison of eating behavior score between mother and their preschoolers showed that mothers' score was lower than their preschoolers' one. Salty foods with high preference and intake frequency by mothers and preschoolers were 'salted dry fish, stock fish' and 'soup, stew, noodle soup'. In addition, there were strong positive correlations between preference and intake frequency on most of the salty food items. Intake of Ramen soup was significantly different (p < 0.001) between the two groups. Preschoolers ate less ramen soup compared to their mothers. Conclusions: Overall results showed that preschoolers' dietary behavior was better than the mothers' one. However, preschoolers' dietary behavior was significantly influenced by their mothers. Therefore, mothers should have an appropriate eating behavior in order to have a positive influence on their children's eating habits. In addition, the results suggested that proper nutrition education is needed for mothers of preschool children.